2013
DOI: 10.5755/j01.ms.19.3.2304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plasticizing admixture on the physical and mechanical properties of concrete with limestone cement

Abstract: The article analyzes the effect of plasticizing admixture content on the physical and mechanical properties of concrete made of 50 % coarse aggregate. The plasticizer dosage levels proposed by the manufacturer (0.2 %-1.2 %) were examined and the optimum plasticizer dose (0.8 %-1.0 %) was established. The use of limestone Portland cement and the optimum content (0.8 %-1.0 %) of plasticizing admixture in the production of concrete increases the compressive strength, density, frost resistance, whereas the water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In plasticized cement pastes of the same initial flow the hydration and hardening process are going faster comparing with non-plasticized. Many authors indicate that PCE slows down the hydration of cement [15,20,21]. In our investigations the more intense hydration, setting and development of hardening structure in plasticized pastes was most likely determined by a considerably lower W/C in them.…”
Section: Discussionsupporting
confidence: 45%
“…In plasticized cement pastes of the same initial flow the hydration and hardening process are going faster comparing with non-plasticized. Many authors indicate that PCE slows down the hydration of cement [15,20,21]. In our investigations the more intense hydration, setting and development of hardening structure in plasticized pastes was most likely determined by a considerably lower W/C in them.…”
Section: Discussionsupporting
confidence: 45%
“…It is widely known that the usage of SP admixture increases mixture`s workability properties [3]. SP content has an effect on the physical, mechanical and structural properties of concrete as well [4]. It is also observed that the workability properties of concrete mixtures can be modified with the addition of mineral additives.…”
Section: Introduction mentioning
confidence: 99%